2009
DOI: 10.1111/j.1751-7893.2009.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Duration of untreated psychosis and pathways to care in patients with first‐episode psychosis in Iran

Abstract: Median DUP was not long in an inpatient sample with first-episode psychosis, which may be due to the preponderance of affective and acute psychoses in this sample and some help-seeking or service variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 28 publications
6
28
0
Order By: Relevance
“…Regarding our study it is worth highlighting that all patients presenting with first psychosis episode were admitted in an acute psychiatric ward, which clinically indicates more severe and acute state without the possibility to manage the psychotic symptoms in an out-patient care settings. This finding is in concordance with observations from other authors on psychosis in acute psychiatric wards (Cratsley et al, 2008;Bhui et al, 2014;Sharifi et al, 2009).…”
Section: Discussionsupporting
confidence: 94%
“…Regarding our study it is worth highlighting that all patients presenting with first psychosis episode were admitted in an acute psychiatric ward, which clinically indicates more severe and acute state without the possibility to manage the psychotic symptoms in an out-patient care settings. This finding is in concordance with observations from other authors on psychosis in acute psychiatric wards (Cratsley et al, 2008;Bhui et al, 2014;Sharifi et al, 2009).…”
Section: Discussionsupporting
confidence: 94%
“…There was a significant relationship between duration of delay in treatment for first symptoms of psychosis and gender which was consistent with findings of Apeldoorn et al (7), Malla et al (14), Sharifi et al (6), and Wunderink et al (9). To put it in other words, in this study, women referred for treatment with shorter delay than men.…”
Section: Discussionsupporting
confidence: 92%
“…That is, Iranian patients used more classical drugs that had positive effects on their symptoms while patients of other countries used more new (atypical) drugs with non-pharmacological treatments. In another research carried out by Sharifi et al (6) to determine duration of untreated psychosis and pathways to care in patients with first-episode psychosis admitted to Roozbeh Hospital, Iran. Findings of this study showed that delay in treatment was not correlated with gender, marital status, level of education of the patient, roommates, number of roommates, and the place of first referral of the patient, but correlated with age, place of residence, and patient's occupation.…”
Section: Introductionmentioning
confidence: 99%
“…Similar proportions of patients initially sought help from psychiatrists (n = 23, 25.3%) as from traditional healers (n = 21, 23.1%), with a smaller proportion seeking help first from a general practioner (n = 16, 17.6%). 8 Causal attributions, pathway to care and clinical features were examined in a sample of 54 firstepisode psychosis patients in South Africa to test if there were associations between these factors and DUP. The results showed that both spiritual attributions of cause (49% of patients) and a previous consultation with a traditional healer (39% of patients) were associated with long DUP.…”
Section: Introductionmentioning
confidence: 99%